The pinstriped prison - Pryor, Lisa. (Sydney : Picador, 2008)
"Why is that so many of the smartest people in Australia get to their thirties and realise that doing everything right has made for an existence they never really wanted? The Pinstriped Prison is a smart, witty look at the consequences of selling your soul"--Provided by publisher.
Machine derived contents note: Prologue: Ambition sans frontieres 1 -- 1 GETTING CAUGHT -- 1 Little lawyers and baby bankers 9 -- 2 Gin and tonics for the gifted and talented 41 -- 3 Recruitment brochure bingo 65 -- 4 Driftnet fishing the intellectual seas 81 -- 5 The joy of spreadsheets 107 -- 6 The private school in the sky 123 -- 2 DOING TIME -- 7 When good jobs turn bad 145 -- 8 Sexism and the city 171 -- 9 The money trap 185 -- 3 PLOTTING AN ESCAPE -- 10 Falling down 209 -- 11 Escapees and refugees 239 -- 12 The real brain drain 261.
Title on cover: The pin striped prison : how overachievers get trapped in corporate jobs they hate.
Keywords: Quality of work life -- Australia; Work -- Psychological aspects; Job satisfaction -- Australia